The Mysterious Chemo-Preventive Player in Oral Cavity: Retinoids - Gatha Mohanty1, Rinkee Mohanty2, Anurag Satpathy3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Vitamin A is considered as one of the essential micronutrients which are extensively associated with chemopreventiveand therapeutic modalities. Carcinogenesis is a complex disease where environmental and geneticfactors act as a predisposing cause bringing about alterations in the overall cell microstructure. Possible roleof Retinoid, which is a form of Vitamin A, has been recognized in suppressing breast cancer, lung carcinoma,cancer of the colon, prostate cancer, blood cancers and to some extent the cancers of the oral cavity. Retinoidis known to act through RAR/RXR receptors to form ligands and thereby affect the transcription processand controls angiogenesis, abnormal proliferation, and metastasis. Some varieties of leukemia have shownbetter results with Retinoid therapy. However its role in oral premalignant and malignant lesions are notmuch known. This review discusses the physiologic, epigenetic and molecular role of Retinoids in lesionsof the oral cavity.